2002
DOI: 10.1093/aje/155.8.732
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease Risks Associated with Cigarette Smoking, Alcohol Consumption, and Caffeine Intake

Abstract: A reduced risk for Parkinson's disease (PD) among cigarette smokers has been observed consistently during the past 30 years. Recent evidence suggests that caffeine may also be protective. Findings are presented regarding associations of PD with smoking, caffeine intake, and alcohol consumption from a case-control study conducted in western Washington State in 1992-2000. Incident PD cases (n = 210) and controls (n = 347), frequency matched on gender and age were identified from enrollees of the Group Health Coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
254
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(277 citation statements)
references
References 32 publications
16
254
2
5
Order By: Relevance
“…Large prospective studies have uniformly shown that the incidence of Parkinson's disease is about 60% lower among current smokers and 40% lower among past smokers than among those who have never smoked, and that the magnitude of the risk reduction diminishes with time since quitting smoking (Hernan et al, 2002(Hernan et al, , 2001. Similarly reduced risk estimates for Parkinson's disease linked with cigarette smoking were observed in large, well-conducted case -control studies (Gorell et al, 1999;Checkoway et al, 2002). These findings led to the hypothesis that constituents of tobacco smoke can reduce or abolish the brain damage that triggers Parkinson's disease.…”
Section: Discussionmentioning
confidence: 92%
“…Large prospective studies have uniformly shown that the incidence of Parkinson's disease is about 60% lower among current smokers and 40% lower among past smokers than among those who have never smoked, and that the magnitude of the risk reduction diminishes with time since quitting smoking (Hernan et al, 2002(Hernan et al, , 2001. Similarly reduced risk estimates for Parkinson's disease linked with cigarette smoking were observed in large, well-conducted case -control studies (Gorell et al, 1999;Checkoway et al, 2002). These findings led to the hypothesis that constituents of tobacco smoke can reduce or abolish the brain damage that triggers Parkinson's disease.…”
Section: Discussionmentioning
confidence: 92%
“…Although many of the case-control studies reported ORs below unity, the association was nonsignificant in most studies [142,143,293,298,303,309,310,380,407,408,410,413,415,423]. A Swedish study that investigated the relationship of PD with beer, wine, and liquor reported inverse associations for each of these types of alcoholic beverages in univariate analyses.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Of the 7 case-control studies that investigated tea intake for a possible association with PD, three reported an inverse association [295,310,358], three found no association [142,144,415], and one reported an increased risk [136]. The Leisure World cohort study and a Finnish cohort study reported no associations [434,481].…”
Section: Coffee and Teamentioning
confidence: 99%
“…For missing inputs, Cochrane effectiveness inputs from a wide range of studies world‐wide were used, and represented rigorous and well‐accepted evidence. Some reported but controversial protective effects of smoking, such as those regarding Parkinson disease 63, 64, 65, 66, 67, 68, 69, 70, 71, were not accounted for in this model. Some diseases attributable to smoking 5 were also not included in the model, as the true impact of smoking could not be estimated, and some interventions available only in the United Kingdom but not in Germany were also not considered.…”
Section: Discussionmentioning
confidence: 99%